Metal additive manufacturing technology for emergency maintenance of field equipment - YANG Lai-xia; DANG Su-wu; WANG Xin-yu (Fenmo yejin jishu)
Metal additive manufacturing technology can be used for the emergency maintenance of field equipment and shows the characteristics of high-usage, high flexibility, and rapidity, which may effectively overcome the defects of the traditional equipment emergency maintenance and improve the emergency support capability of field equipment. The forming efficiency, forming accuracy, and mechanical property of the common metal additive manufacturing technology were compared in this paper. Combined with the application status at home and aboard of the metal additive manufacturing technology in the field of equipment maintenance and the characteristics of the emergency maintenance of field equipment, the forming quality, forming ability, equipment mobility, and anti-jamming ability were analyzed. The conclusion was shown that the laser cladding deposition (LCD) and wire and arc additive manufacturing (WAAM) were more suitable for the emergency maintenance of field equipment. Finally, the existing problems and the future trends of LCD and WAAM used for the mergency maintenance of field equipment were discussed.